A Comprehensive Review on MAPK: A Promising Therapeutic Target in Cancer - Braicu, Cornelia; Buse, Mihail; Busuioc, Constantin; Drula, Rares; Gulei, Diana; Raduly, Lajos; Rusu, Alexandru; Irimie, Alexandru; Atanasov, Atanas G; Slaby, Ondrej; Ionescu, Calin; Berindan-Neagoe, Ioana (Cancers, 2019)
The mitogen-activated protein kinase (MAPK) pathway is an important bridge in the switch from extracellular signals to intracellular responses. Alterations of signaling cascades are found in various diseases, including cancer, as a result of genetic and epigenetic changes. Numerous studies focused on both the homeostatic and the pathologic conduct of MAPK signaling; however, there is still much to be deciphered in terms of regulation and action models in both preclinical and clinical research. MAPK has implications in the response to cancer therapy, particularly the activation of the compensatory pathways in response to experimental MAPK inhibition. The present paper discusses new insights into MAPK as a complex cell signaling pathway with roles in the sustenance of cellular normal conduit, response to cancer therapy, and activation of compensatory pathways. Unfortunately, most MAPK inhibitors trigger resistance due to the activation of compensatory feed-back loops in tumor cells and tumor microenvironment components. Therefore, novel combinatorial therapies have to be implemented for cancer management in order to restrict the possibility of alternative pathway activation, as a perspective for developing novel therapies based on integration in translational studies.
Keywords: molecular mechanisms; cancer; MAPK; drug resistance